An investigation of the pollution load caused by trout breeding in Karakaya Dam Lake in Turkey - Ornekci, Nedim Gurel; Uslu, Gulsad; Uslu, Ali Atilla (American Society of Agricultural and Biological Engineers, 2013)
Trout farming has showed a rapid increase in Karakaya Dam Lake established on the Euphrates River in Diyarbakir Province in Turkey, which started to affect the water quality parameters and environmental carrying capacity of the lake. Therefore, this study was carried out to determine water quality of Karakaya Dam Lake. Water samples were taken from 3 different depths and at 5 sampling points in Karakaya Dam Lake for a period of one year. Around these locations, there are 38 facilities producing 6.000 ton trout/year. Evaluations have been done on trout culture, carrying capacity and trophic level of the lake by considering the obtained results. Water samples were analyzed for the parameters of temperature, pH, dissolved oxygen, total phosphorus, ammonia, and chemical oxygen demand (COD). Results show that there wasn't significant issue except flow rate and temperature changes, which will negatively affect aquaculture in terms of water quality. In addition, phosphorus was element in limiting the growth of algae Karakaya Dam Lake. With the significant decrease in flow rate in the summer months, the increase in water temperature limits trout production capacity. Thus, water quality and production potential concerning aquaculture were determined in the lake. After the findings of the physical and chemical analyses were compared, it was observed that Karakaya Dam Lake has oligotrophic lake characteristics. In the lights of these results, it can be concluded that Karakaya Dam Lake generally has a convenient habitat with regard to aquaculture.
American Society of Agricultural and Biological Engineers Annual International Meeting 2013 -- 21 July 2013 through 24 July 2013 -- Kansas City, MO -- 98427
Keywords: Cage fishing; Karakaya Dam Lake; Nutrient; Oligotrophic lake; Water quality